Wireless Sensor Network Nodal Development for Low Cost and Low Power PH Soil Monitoring Agriculture 4.0 Application - Galang Hakim; muhammad Hafidz; Ahmad Firdausi; Eko Ramadhan (Journal FORTEI-JEERI, 2020)
According to a report from the United Nations estimates that by 2030 about 800 million people worldwide will suffer from hunger. To combat this problem the agricultural production needs to be increased by at least 60%. One of many parameters that need to be monitor to increase agricultural output was soil PH level. Soil PH is very influential on the development of rice plants, where high acidity soil will make plant unhealthy and die. In order to be able monitor soil PH level, we need low cost and long life WSN node that can monitor soil PH level. In this paper we have manage to a long life WSN node that can monitor PH level with low cost at about less than 15 US dollar. this WSN node PH meter are using couple of aluminum and lead couple electrode as sensor, and its deviation at about 0.73 compare with ATC 009 PH meter which only 0.55. This device also capable to operate for so long (which is 2 years operational time) using 0.1 duty cycle scheme.